PANoptosis-related genes in rheumatoid arthritis synovial tissue: screening, validation, and functional implications - Lu, Yunmi; Yang, Jiaxin; Deng, Yasi; Chen, Yuxin; Zhang, Ke; Ouyang, Liangcheng; Zhai, Yuge; He, Jinbo; Wang, Chenxu; Huang, Juan; Wang, Wei; Yu, Huanghe (Frontiers in Immunology, 2026)
ObjectiveTo screen and validate the expression of key PANoptosis-related genes in the synovial tissue of rheumatoid arthritis (RA) through bioinformatics approaches and in vitro/in vivo experiments, explore their role in RA synovial hyperplasia, and provide new targets for RA treatment.MethodsBased on multiple genomic datasets from the GEO database, differentially expressed genes (DEGs) were screened using tools such as the limma package. The STRING database and Cytoscape 3.7.0 were employed to construct a Protein-Protein Interaction (PPI) network, followed by Gene Ontology (GO) functional annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis. Meanwhile, the CIBERSORT algorithm was used to perform immune infiltration analysis on the merged dataset to evaluate the proportional differences of 22 immune cell subsets. Classic in vitro and in vivo RA models (RA Fibroblast-Like Synoviocytes (RAFLSs) and adjuvant-induced arthritis (AIA) rat model) were established to investigate the expression of DEGs with high diagnostic value in RA synovial tissue.ResultsThirteen key DEGs involved in the PANoptosis pathway were identified in RA. GO and KEGG enrichment analyses showed that these genes were mainly involved in the NOD-like receptor signaling pathway and apoptosis signaling pathway. Immune infiltration analysis revealed significant differences in the immune microenvironment between RA patients and healthy controls: the RA group showed significant enrichment of pro-inflammatory immune cell subsets, while the control group was enriched with cells with inhibitory or homeostasis-maintaining functions. Compared with normal rats, the synovial tissue of AIA rats exhibited obvious abnormal hyperplasia. Western Blot (WB) results indicated that, compared with the control group, the expression levels of IL-18, NLRP3, GBP1, TNFSF10, Caspase-1, and Bcl-2 proteins in RAFLSs and AIA rat synovial tissue were significantly increased, while the expression levels of Bax and Caspase-3 were significantly decreased.ConclusionDuring the pathogenesis of RA, the key PANoptosis markers (IL-18, NLRP3, GBP1, TNFSF10, Bax, Bcl-2, Caspase-1, and Caspase-3) are involved in invasive synovial hyperplasia. The characteristic immune cell imbalance in RA provides conditions for these key PANoptosis markers to regulate immune cell functions, and it is an important basis for the pathological changes of joint synovial hyperplasia in RA.